ANALISIS PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - B11108072, Syarifah Meliyani (Jurnal Manajemen Update, 2012)
Profitability is an indicator for the performance and capabilities in utilizing all business entities owned property to generate profit. Assessment of the profitability of a business entity can be measured through Return on invesment (ROI), is the return on investment in assets.This research study on the effect of financial ratios including liquidity ratio (quick ratio and current ratio) and the solvency ratio (debt assets ratio and debt equity ratio) to profitability (ROI) in the food and beverages industry which is registered in the BEI. Purpose of this research are to know the impact of liquidity ratios and solvency ratios, both simultaneously and partially to the profitability of the food and beverages industry wich is registered in the BEI, and to find out what ratios among these has a dominant effect on profitability. This research used documentary techniques and library research as well as using multiple regression analysis method t test, f test dan beta coefficients a method of data analysis. Keywords :profitability ratio, liquidity ratio, solvency ratio